B‐cell activating factor, a predictor of antibody mediated rejection in kidney transplantation recipients. Issue 2 (18th January 2018) - Pongpirul, Wannarat; Chancharoenthana, Wiwat; Pongpirul, Krit; Leelahavanichkul, Asada; Kittikowit, Wipawee; Jutivorakool, Kamonwan; Nonthasoot, Bunthoon; Avihingsanon, Yingyos; Eiam‐Ong, Somchai; Praditpornsilpa, Kearkiat; Townamchai, Natavudh
Abstract: Aim: Donor‐specific antibody (DSA) is a widely‐used biomarker for antibody‐mediated rejection (ABMR) but correctly indicates only 30–40% of patients with ABMR. Additional biomarkers of ABMR in kidney transplant recipients are needed. Methods: All 68 kidney transplanted‐recipients enrolled in this study were negative for graft rejection as determined by surveillance‐biopsy ELISA at day 7 post‐transplantation. Allograft biopsy was then performed at 6 months post‐transplantation for subclinical‐ABMR detection. Recipients were stratified by pre‐transplant DSA and BAFF at day 7 into four groups. Results: During the study period, 13.2% of the recipients demonstrated subclinical‐ABMR at 6 months, without patient with clinical ABMR presentations. Overall mean BAFF at day 7 was 393 pg/mL (95% CI = 316–471 pg/mL). The optimal cut‐off value for low vs. high BAFF level was 573 pg/mL, with sensitivity and specificity at 77.8% and 88.1%, respectively. Fifty percent of recipients with high BAFF at day 7 (14 patients) and only 3.7% of patients with low BAFF demonstrated ABMR ( P <  0.05). Indeed, ABMR was more common in patients high BAFF level (hazard ratio = 7.30; 95% CI = 3.77–14.15). The prevalence of ABMR among negative pre‐transplant DSA/low BAFF, positive DSA/low BAFF, negative DSA/high BAFF, and positive DSA/ high BAFF recipients were 4.4, 0, 37.5 and 66.7%, respectively ( P <  0.05). Conclusions: Post‐transplant ABMR can be predicted by perioperative serum BAFF level. Together with DSA testing, BAFF provides additional predictive value for ABMR. Summary at a Glance: In this paper serum measurement of the B cell activating factor (BAFF) was studied as a potential marker of antibody mediated rejection, suggesting that in addition to measurement of DSA this novel biomarker may be helpful in predicting ABMR.